An Analysis of the Persian Translation of the Alchemist by Paulo Coelho, Based on Juliane House’s (1997) Quality Assessment Model of Translation - Sheida Ronagh Zadeh; Azadeh Nemati; Mohammad Bavali (Universitas Islam Negeri Walisongo Semarang, 2020)
As quality is one of the most important aspects of translation studies, the researchers aim at analyzing the quality of the Persian translation of The Alchemist by Paulo Coelho, which is one of the best-selling novels in the world based on House’s (1997) model of translation quality assessment. As it was time-consuming to apply this model to the whole book, twenty sections out of forty-five sections of the English version were selected randomly. In this qualitative-descriptive research, both source text and target text were compared in tables regarding quality. The study revealed that the translator had translated the text overtly, confirming House’s idea, who noted that literary texts should be translated overtly. However, the cultural filter was applied to some parts of the text that were not acceptable in the target culture. Therefore, covert translation was acceptable in some parts. According to the analysis based on House’s model, the Persian translation was almost of good quality. The register, as well as the related sub-branches, was observed well in most parts of the target text. The text, in respect of textual means, was also cohesive and coherent; however, the lexical choice in some parts needed improvement. The researchers also found out that some part of the source text information was not transferred to the target text without any particular reasons. Thus, it was illustrated that although House’s translation quality assessment model is the best translation quality assessment model among other models, it needs improvement. House’s model was not able to analyze the text in respect of information transfer. Therefore, this could be a weak point in House’s model. In short, the translated text was not of high quality as it needs improvement in respect of information transfer and lexical choice.